2004
DOI: 10.1111/j.1600-6143.2004.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of A3 Adenosine Receptor Provides Lung Protection Against Ischemia-Reperfusion Injury Associated with Reduction in Apoptosis

Abstract: Apoptosis has been described in various models of ischemia-reperfusion (IR) injury, including lung transplantation. A 3 adenosine receptor (AR) has been linked to a variety of apoptotic processes. The effect of A 3 AR activation on lung injury and apoptosis, following IR, has not been reported to date. In a spontaneously breathing cat model, in which the left lower lobe of the lung was isolated and subjected to 2 h of ischemia and 3 h of reperfusion, we tested the effect of IB-MECA, a selective A 3 AR agonist,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 52 publications
4
34
0
Order By: Relevance
“…Similar findings were reported in a study that demonstrated increased inflammation in A 3 R 2/2 mice subjected to an air-pouch model of acute inflammation (38). In addition, our observations are consistent with findings in in vivo models of injury, including lipopolysaccharide-induced endotoxemia (39), adjuvant-induced arthritis (40), colitis (41), and ischemic injury in the lung (42), where A 3 R activation has been shown to suppress inflammatory processes. Thus, our findings strengthen the notion that the A 3 R plays an important role in regulating the degree of inflammation after injury.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings were reported in a study that demonstrated increased inflammation in A 3 R 2/2 mice subjected to an air-pouch model of acute inflammation (38). In addition, our observations are consistent with findings in in vivo models of injury, including lipopolysaccharide-induced endotoxemia (39), adjuvant-induced arthritis (40), colitis (41), and ischemic injury in the lung (42), where A 3 R activation has been shown to suppress inflammatory processes. Thus, our findings strengthen the notion that the A 3 R plays an important role in regulating the degree of inflammation after injury.…”
Section: Discussionsupporting
confidence: 92%
“…In preclinical testing, the A 3 AR agonist IB-MECA was shown to protect against lung injury and apoptosis in cats after reperfusion 178 , and this protection was antagonized by MRS1191, a dihydropyridine that is a selective A AR antagonist 56 As described earlier, prominent species differences in the structure and function of ARs, especially the A 3 AR, have been observed. For example, human and rat A 3 ARs only share 72% overall identity at the amino-acid level; mast-cell degranulation is induced by the A 2B AR in dogs and humans, but by the A 3 AR in mice.…”
Section: Ars As Targets In Pulmonary Disordersmentioning
confidence: 72%
“…Neutrophils, in particular accelerate lung tissue damage by furthering the breakdown of the endothelial cell barrier through the production of a number of potent proteolytic enzymes and reactive oxygen species that directly lead to cell death (2). Loss of integrity of endothelial cell barrier leads to pulmonary edema and compromised blood oxygenation (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%